2012
DOI: 10.1038/cdd.2011.183
|View full text |Cite
|
Sign up to set email alerts
|

Programming of adipose tissue miR-483-3p and GDF-3 expression by maternal diet in type 2 diabetes

Abstract: Nutrition during early mammalian development permanently influences health of the adult, including increasing the risk of type 2 diabetes and coronary heart disease. However, the molecular mechanisms underlying such programming are poorly defined. Here we demonstrate that programmed changes in miRNA expression link early-life nutrition to long-term health. Specifically, we show that miR-483-3p is upregulated in adipose tissue from low-birth-weight adult humans and prediabetic adult rats exposed to suboptimal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 40 publications
3
121
0
4
Order By: Relevance
“…13 Additional miR-483-3p target genes including BBC3/ PUMA, SMAD4, CTNNB1 and GDF3 have been identified in other tissues (Wilm's tumors, adrenocortical carcinomas, HCT116 colon and HepG2 hepatocellular carcinoma cell lines, and adipose tissue). [14][15][16][17][18] We demonstrate now that CDC25A has a key role in the mediation of the anti-proliferative effects of miR-483-3p in keratinocytes by controlling the binding between CDK6/4 and CCNDs. Our results obtained on CDK6 shed new light on the mechanisms that control CCND-CDK6/4 assembly in early G1, showing that this association greatly depends on the phosphorylation status of the Y residues located in the 'Glycin rich domain' of these kinases.…”
mentioning
confidence: 64%
“…13 Additional miR-483-3p target genes including BBC3/ PUMA, SMAD4, CTNNB1 and GDF3 have been identified in other tissues (Wilm's tumors, adrenocortical carcinomas, HCT116 colon and HepG2 hepatocellular carcinoma cell lines, and adipose tissue). [14][15][16][17][18] We demonstrate now that CDC25A has a key role in the mediation of the anti-proliferative effects of miR-483-3p in keratinocytes by controlling the binding between CDK6/4 and CCNDs. Our results obtained on CDK6 shed new light on the mechanisms that control CCND-CDK6/4 assembly in early G1, showing that this association greatly depends on the phosphorylation status of the Y residues located in the 'Glycin rich domain' of these kinases.…”
mentioning
confidence: 64%
“…There is now accumulating evidence that translational repression of miRNA targets is the primary event in the mechanism; several groups have demonstrated that repression can be seen without the necessity for mRNA degradation. [58][59][60][61][62][63][64][65] In vitro studies showed that miRNA-mediated repression is a two-step process, the first of which affects translation of the target mRNA. 59,66 These were followed by a series of reports that employed temporal studies to demonstrate that translational repression of miRNA targets precedes deadenylation and degradation in Drosophila, zebrafish and mammalian cells.…”
Section: Steps To Repressionmentioning
confidence: 99%
“…Furthermore, nutrient-dependent modulation of microRNAs (miRNAs) may also trigger disease susceptibility and metabolic complications in offspring. Indeed, misexpressed miRNAs participate in the programming of adipose tissue in rats with retarded growth, causing lipotoxicity and insulin resistance, and hence they increase the susceptibility to metabolic disease during adulthood (10).…”
mentioning
confidence: 99%